(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
In this study the Surface layer (S-layer) protein was extracted from Aeromonas hydrophila bacteria ,the humoral immune response that induced by S-layer protein only or as adjuvant was investigated by using 16 males New Zealand rabbits and divided into four groups, each group contained four rabbits, the first group was immunized with S-layer protein only, the second group was immunized with heated killed antigen(HKA)of Sallmonella typhi only, the third group was immunized with mixed antigens (S-layer+ HKA),while the fourth group considered as control group and immunized with normal saline. The HKA of S. typhi was used to evaluate the efficiency of S-layer protein as adjuvant. After the immunization period, the humoral immune response was investigated by several tests include, tube agglutination test and passive agglutination test that used to detect the antibody titer. Biuret method was used to determine the total protein concentration in serum samples and total protein concentration of secretory immunoglobulin that extracted form appendix samples. In addition the Radical Immunodiffution (RID) method was used to detect the concentration level of the IgG in serum samples. Moreover the concentration level of the CD4 in the serum samples was determined by enzyme linked immunosorbent assay (ELISA) method .In all these tests the result revealed, both of S-layer protein only , HKA of only and mixed antigens(S-layer+ HKA) were given significantly increased in comparison with control group at P<0.05. The result showed that the concentration level of IgG with mean values (2365.5 , 3505 and 2916) mg/dl respectively while the control group with mean value (1662)mg/dl. In addition the concentration level of CD4 molecule with mean values (9.37, 11.77 and 17.36) ng/ml respectively while the control group with mean value (6.91) ng/ml .The results showed that these three types of antigens induced the humoral immune response